VD_FINDINFO HC / 2013 / 346 vom 14. Mai 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, DIVORCE SUR DEMANDE UNILATÉRALE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT, MINIMUM VITAL | 125 CC, 163 al. 2 CC, 176 al. 1 ch. 1 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 316 al. 3 CPC (CH), 317 al. 1 CPC (CH), 334 al. 1 CPC (CH)